218k views
1 vote
Bell WorkDIRECTIONSSolve the equation for the variable x.-2(x-3) = 26*Hint: Make sure to use distribution arrows and identifylike terms.

User Nmax
by
5.0k points

1 Answer

0 votes

You have the following equation:

-2(x - 3) = 26

in order to solve the previous equation, proceed as follow:

-2(x - 3) = 26 use distribution property

-2(x) - 2(-3) = 26

-2x + 6 = 26 subtract 6 both sides

-2x = 26 - 6 simlify like terms right side

-2x = 20 divide by -2 both sides

x = 20/(-2)

x = -10

Hence, the solution to the given equation is x = -10

User Krishna Jangid
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.